Elucidating the physiological and biochemical responses of different tobacco (Nicotiana tabacum) genotypes to lead toxicity. (26th July 2016) - Maodzeka, Antony; Hussain, Nazim; Wei, Liquan; Zvobgo, Gerald; Mapodzeke, James Mutemachani; Adil, Muhammad Faheem; Jabeen, Salma; Wang, Feng; Jiang, Lixi; Shamsi, Imran Haider
Abstract: In the present study, the effects of lead (Pb) uptake and toxicity were investigated in a hydroponic culture using 7 tobacco ( Nicotiana tabacum L.) genotypes (Bina 1 [B1], Kutsaga Mammoth 10 [KM10], Nanjing 3 [N3], Kutsaga 35 [K35], Kutsaga E1 [KE1], Cocker 176 [C176], and Kutsaga RK6 [KRK6]) that differed in Pb tolerance. Lead was applied as a solution of Pb nitrate at concentrations of 0 μM, 10 μM, 250 μM, and 500 μM. After 4 wk of Pb treatment, tissue biomass and photosynthetic parameters were measured and elemental analysis was performed. The results showed decreases in growth and photosynthetic parameters with increases in Pb concentration compared with the control. The least reduction in the recorded physiological parameters was noted in K35, whereas the greatest reduction was observed in N3, which is an obvious indication of genotypic differences. Activities of peroxidase, catalase, and malondialdehyde increased significantly with increases in Pb concentration, with genotypes K35 and N3 showing the least and the greatest reduction, respectively. The results demonstrate the phototoxic nature of Pb on plants, and it can be concluded that in Pb‐prone areas genotypes K35 and B1 can be used for cultivation because they can grow efficiently in the presence of high Pb concentrations while restricting Pb uptake in the aboveground parts, as seen by the higher Pb tolerance index. Environ Toxicol Chem 2017;36:175–181. © 2016 SETAC